Pengaruh Customer Trust dan Customer Satisfaction Terhadap Brand Loyalty Melalui E-WOM - Abdul Hamid; Mokhammad Natsir; Harianto Respati (Universitas Yudharta Pasuruan, 2022)
(English Version) In the midst of the times, the competition is very tight, making the company trying to maintain its business continuity. So, producers should seek various ways to maintain customer satisfaction and loyal customers to AFB Advertising. The type of research used is explanatory research. The population in this study is AFB Advertising customer. The sample technique used purposive sampling as many as 105 people as respondents. This study uses a questionnaire as a data collection instrument whose results will be analyzed using the Structural Equation Model (SEM) equation model with path analysis. The results of his research show that: (1) Customer trust and customer satisfaction have a significant effect on brand loyalty through E-WOM which has an E-WOM beta coefficient value of (α = 0.05). (2) Customer trust is determined by trusting belief and trusting intention. Then, customer satisfaction is determined by service quality, personal selling and complaint handling. However, E-WOM is determined by intensity, valence of opinion and content. Brand loyalty is determined by information sharing, positive information, Friend recomendation, and continuing purchase. Then, Brand Loyalty affects Share Information. (Versi Indonesia) Di tengah perkembangan zaman persaingan sangat ketat menjadikan perusahaan berupaya untuk mempertahankan kelangsungan bisnisnya. Sehingga produsen harus mengupayakan berbagai cara untuk menjaga kepuasan konsumen dan pelanggan yang setia terhadap AFB Advertising. Jenis penelitian menggunakan penelitian eksplanatori dengan populasi dari customer AFB Advertising. Teknik sampel menggunakan purposive sampling sebanyak 105 orang sebagai responden. Penelitian ini menggunakan kuesioner sebagai instrumen pengumpulan data yang hasilnya akan dianalisis dengan menggunakan model persamaan Structural Equation Model (SEM) dengan Path Analysis. Hasil penelitiannya menunjukkan bahwa: (1) Customer Trust dan Customer Satisfaction berpengaruh signifikan terhadap brand loyalty melalui E-WOM memiliki nilai koefisien beta E-WOM sebesar (α = 0,05); (2) Customer trust ditentukan oleh Trusting Belief dan Trusting Intention, Customer Satisfaction ditentukan oleh service quality, personal selling dan complain handling serta E-WOM ditentukan oleh Intensity, Valence Of Opinion dan Content kemudian Brand Loyalty ditentukan oleh Share Information, Say Positif Things, Recommended Friends dan Continue Purchasing. Brand Loyalty berpengaruh terhadap Share Information.